Reliability of the Fitness Gram test in Assessing Physical Fitness among School Children in Guwahati, North-east India - Gogoi, Pranjal; Bhattacharyya, Nirmal C. (Disease and Health Research - New Insights Vol. 1, 2024)
Background: The physical fitness is an integrated measure of the body functions involved in the performance of daily physical activity and physical exercise. Childhood and adolescence are crucial periods of life, where physiological and psychological changes take place at these age. Both cardiorespiratory and muscular fitness in children are important for positive health behaviour. The assessment of physical fitness using a specific tool has become an important part to find out the fitness level of children and adolescence. Fitness gram is a health-related fitness test that utilizes criterion-referenced standards on health-related components. Through the years research has shown that Fitness gram has become one of the most widely used programs in the United States, though its use in India is not popular.This study aims to evaluate the interrater reliability of the Fitness Gram test, a widely used tool for physical fitness assessment, among school children in the urban society of Guwahati, North-East India. Methods: A sample of 70 school children aged 5-14 years was assessed using the Fitness gram test battery. Students were randomly allocated for physical fitness test where 62 students have completed the test.Two trained raters independently scored the tests. Statistical analysis was done by Cronbach’s Alpha value has been computed for the Interrater reliability. Results: Sixty-two students with both gender (male 56.3% and female 43.7%, age -10.12±2.72) were assessed for physical fitness using Fitness gram test battery. All the test variables showed an excellent reliability (Cronbach’s alpha =0.91-0.95). Conclusions: Fitness Gram test demonstrates high interrater reliability for assessing physical fitness in school children in Guwahati. These findings support its use as a reliable tool in school-based fitness assessments, potentially aiding in the development of targeted fitness programs.